The Capture Effect of Yellow Sticky Traps of Different Tones on Agalmatium bilobum (Fieber, 1877) (Hemiptera: Auchenorrhyncha: Issidae) in Almond Orchards - Ozgen, Inanc; Gnezdilov, Viladimir M. (Gazi Entomological Research Soc, 2022)
This study was conducted to determine the effects of yellow traps of different tones against Agalmatium bilobum (Fieber, 1877) (Hemiptera: Auchenorrhycha: Issidae: Hysteropterinae) in almond orchards in Yurtbasi District of Elazig Province between May to July of 2018. In this study, planthopper individuals were caught in eight different yellow-toned traps and counted for 14 days. It has been determined that most planthopper individuals were attracted by the yellow color tone with trap codes 1016 (4) and 0279 (5). It is considered that this color tone is mostly effective for the attraction of A. bilobum in almond orchards. Accordingly, positive results can be obtained from using this kind of yellow tone trap by the producers to prevent the harm of A. bilobum to almonds. To the best of our knowledge, this is the first report related to the capture effect of yellow sticky traps on the Issidae species .
Keywords: Hysteropterinae; planthopper; sticky trap; colour tone; almond; Turkey